Estudo dos subprodutos do maracujá (Passiflora edulis f. flavicarpa Deg.) - Pontes, Marco Antonio Nobre (1985)
To accomplish this work we used skins and seeds from the yellow passion fruit (Passiflora edulis f. flavicarpa Deg.) [...]